2018
DOI: 10.1016/j.neuropsychologia.2017.12.002
|View full text |Cite
|
Sign up to set email alerts
|

A new insight into sentence comprehension: The impact of word associations in sentence processing as shown by invasive EEG recording

Abstract: The effect of word association on sentence processing is still a matter of debate. Some studies observe no effect while others found a dependency on sentence congruity or an independent effect. In an attempt to separate the effects of sentence congruity and word association in the spatio-temporal domain, we jointly recorded scalp- and invasive-EEG (iEEG). The latter provides highly localized spatial (unlike scalp-EEG) and high temporal (unlike fMRI) resolutions. We recorded scalp- and iEEG in three patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 73 publications
(109 reference statements)
2
3
0
Order By: Relevance
“…In ECoG, the said effect was most pronounced in later time-windows (in particular during the N400) and was spatially localized mainly in the left superior and middle temporal gyri and, to a considerably lesser extent, in the right temporal cortex (middle temporal and fusiform gyri). This observation suggests that semantic priming reflected by the N400 ERP is mainly concentrated in the left temporal cortex, as previously reported (Khachatryan et al, 2018;Ghosh Hajra et al, 2018).…”
Section: The Difference In Spatiotemporal Dynamics Of Semantic and Perceptual Priming Effectssupporting
confidence: 86%
See 3 more Smart Citations
“…In ECoG, the said effect was most pronounced in later time-windows (in particular during the N400) and was spatially localized mainly in the left superior and middle temporal gyri and, to a considerably lesser extent, in the right temporal cortex (middle temporal and fusiform gyri). This observation suggests that semantic priming reflected by the N400 ERP is mainly concentrated in the left temporal cortex, as previously reported (Khachatryan et al, 2018;Ghosh Hajra et al, 2018).…”
Section: The Difference In Spatiotemporal Dynamics Of Semantic and Perceptual Priming Effectssupporting
confidence: 86%
“…This is additionally supported by the observed ERSs in the alpha band during the said time windows in response to primes and ERDs in response to related targets, as an increase in alpha power has been linked to inhibition (Klimesch, 2012). Some previous studies (Khachatryan et al, 2018;Migliaccio et al, 2016) suggest the involvement of the middle part of the left middle temporal gyrus (mMTG) in semantic processing and locate the semantic hub in the anterior temporal cortex (ATL) (Patterson et al, 2007), also based on observations of N400 in that area (Lau et al, 2013;Jackson et al, 2015). In the current study, we observed an N400 effect in the left middle temporal cortex spanning to ATL, as well as an increase in high-gamma power around the N400 time window in response to related targets, which confirms the involvement of this area in semantic processing.…”
Section: Time-frequency Analysis Reveals the Effect Of Context On Object Processingsupporting
confidence: 62%
See 2 more Smart Citations
“…2010 ; Ponz et al. 2013 ; Khachatryan et al. 2018 ) studies and that, assuming average response latencies in the order of 700 ms, trials would be roughly 2000 ms apart from each other.…”
Section: Methodsmentioning
confidence: 99%